2006
DOI: 10.1111/j.1399-3046.2005.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric liver transplantation using left hepatic segments from living related donors: Surgical experience in 100 recipients at Saint‐Luc University Clinics

Abstract: Living-related liver transplantation was developed in the context of deceased donor organ shortage, which is particularly acute for pediatric recipients. This retrospective study analyzes the surgical technique and complications in the first 100 pediatric liver transplantation using left segmental liver grafts from living donors, performed at Saint-Luc University Clinics between July 1993 and April 2002. Pre-operative evaluation in donors and recipients, analysis of the surgical technique, and postoperative co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 25 publications
4
80
0
1
Order By: Relevance
“…The technical details of the DD whole, reduced-size and split liver grafts were previously reported (7,10). The University of Wisconsin preservation solution was used for graft preservation in both groups.…”
Section: Surgical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The technical details of the DD whole, reduced-size and split liver grafts were previously reported (7,10). The University of Wisconsin preservation solution was used for graft preservation in both groups.…”
Section: Surgical Methodsmentioning
confidence: 99%
“…The University of Wisconsin preservation solution was used for graft preservation in both groups. The liver grafts retrieved from the LD were transplanted orthotopically in the recipients, following a surgical procedure recently described in detail (7). In case of portal vein hypoplasia, a jump venous graft was implanted between the recipient superior mesenteric vein and the portal vein of the liver graft, this venous graft being either the recipient left internal jugular vein or a preserved iliac vein from a DD (7).…”
Section: Surgical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9] The following surgical characteristics were collected: total, cold, and warm (anastomosis) ischemia times; number of hepatic arteries in the graft; number of reconstructed hepatic arteries and number of ligated arteries in the graft; number of biliary anastomoses; site of the biliary anastomosis [common bile duct (CBD), common hepatic duct (CHD), or left hepatic duct (LHD)]; type of biliary reconstruction (hepaticojejunostomy, duct-to-duct anastomosis, or hepaticoduodenostomy); and type of abdominal wall closure (primary or secondary). Biliary reconstruction was most frequently performed with Roux-en-Y hepaticojejunostomy (n 5 396 or 92%) or a duct-to-duct anastomosis (n 5 22 or 5%) without the use of a biliary drain or stent.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Although deceased donor liver transplantation is considered a standard procedure, living donor liver transplantation (LDLT) has been widely performed owing to the shortage of donors [4] . LDLT is technically demanding because of the use of short vascular pedicles, which are more likely to cause postoperative vascular complications, such as hepatic venous outflow obstruction (HVOO) at the anastomotic site and anastomotic portal vein stenosis (PVS) [5][6][7][8] . Moreover, biliary complications remain common after LDLT, and some studies suggested that biliary stricture at the anastomotic site occurs more frequently in post-LDLT patients than in deceased liver transplantation.…”
Section: Introductionmentioning
confidence: 99%